Demand Side Factors Associated With Quality Antenatal Care Services: A Case Study of Lusaka District, Zambia - Katemba, Brave M.; Bwembya, Phoebe; Hamoonga, Twaambo E.; Chola, Mumbi; Jacobs, Choolwe (Frontiers in Public Health, 2018)
Background: The quality of antenatal care (ANC) a woman receives during pregnancy is crucial to both the child and the mother’s life. It has been established that providing high-quality ANC can save lives and has a positive impact on postnatal health care services. However, the quality of ANC in Zambia requires attention as maternal and neonatal mortality rates are still unacceptably high with Lusaka district not being left out of the problem. Methods: Using a cross-sectional study design, the main aim of this study was to determine the demand side factors associated with high-quality antenatal care among pregnant women in Lusaka. It also estimated the proportion of women who received high-quality ANC during their last antenatal visit. Multifactorial logistic regression model was fitted in STATA version 13 to predict the demographic, socio and economic factors that influence the quality of ANC. Results: It was established that only 47.1% of pregnant women received high-quality ANC while 52.9% received low quality. Six key ANC interventions were considered, among which urine (36.7%) and blood (46.8%) testing were the least received basic components of ANC. After adjusting for the effect of other factors, women with secondary education had higher odds of receiving high-quality ANC than women with primary level of education (OR = 1.98; 95% CI: 1.24 to 3.14). Women staying with their husband/partners had lesser odds of receiving high quality ANC compared to those that were not staying with their partners (OR = 0.47; 95% CI: 0.28 to 0.79). Conclusion: The quality of antenatal care received by pregnant women in Lusaka is low. Continued efforts to improve the delivery of basic ANC services such as blood and urine testing is required to improve the quality of healthcare services provided by medical personnel at all levels.